(3GdSde GdeQhfbs - (3GdCNVQj, YHO GdQMef Hf eMeO Hf eMeO J (B983 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj bO CNQLG fJGjL GdacQ dCQHGH GdMLG hMW Yfge ef SeGA GdYbd cd MLGH ef SMGH GdLgd s
(3BNQgG (B:s
(3hBdg hUMHg GdKbGJ GdSGdcjf SHd GdfLGI eG bWYJ TeS GdfgGQ CHQGMG hWdY GdHOQ GdefjQ aj GdOLGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 331s
(3eYLe GdeDdajf (B2 /119s
(3cTa GdXfhf (B2 / 998s
(3gOjI GdYGQajf (B6 / 546s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs